Investigation of dependence of the optical fiber dispersion on duration of the compressive impact - Orazymbetova А.К. (Recent Contributions to Physics, 2015)
Unbalanced tensions can appear in the fiber-optic cable (FOC) during the laying and maintenance of it, these tensions can even increase at improper winding and installation of the cable. The article presents the results of experimental investigations of dependence of radiation pulse duration on the compressive force acting on a multimode optical fiber. It is found that the external influence factors impact significantly on the parameters of the optical fibers. It is shown that the spreading of pulse duration is caused by birefringence and scattering at nanopores, and the processes of pulse duration increase are accelerated if the light guide is under constantly increasing load.